2018
DOI: 10.1111/ejn.14165
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the neural pathway from the dorsolateral bed nucleus of the stria terminalis to the central amygdala induces anxiety‐like behaviors

Abstract: The bed nucleus of the stria terminalis (BNST) and the central amygdala (CeA) comprise a forebrain unit that has been described as the “extended amygdala”. These two nuclei send dense projections to each other and have been implicated in the regulation of negative emotional states, including anxiety and fear. The present study employed an optogenetic technique to examine whether stimulation of CeA‐projecting dorsolateral BNST (dlBNST) neuron terminals would influence anxiety‐like behaviors in male Sprague‐Dawl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 33 publications
3
22
0
Order By: Relevance
“…The CeA is an important region of the amygdala, orchestrating a diverse set of behaviors, including fear, anxiety, and defensive responses [ 2 , 42 , 43 ]. Our rabies virus input-tracing identified several principal input regions reported in previous studies, such as the PVT [ 44 ], AI [ 45 ], BST [ 46 ], and substantia nigra pars compacta [ 47 ] (Figs 4 and 5 , Table S1). Projections from the lateral parabrachial nucleus to the CeA may be essential for sodium intake [ 48 – 50 ].…”
Section: Discussionmentioning
confidence: 54%
“…The CeA is an important region of the amygdala, orchestrating a diverse set of behaviors, including fear, anxiety, and defensive responses [ 2 , 42 , 43 ]. Our rabies virus input-tracing identified several principal input regions reported in previous studies, such as the PVT [ 44 ], AI [ 45 ], BST [ 46 ], and substantia nigra pars compacta [ 47 ] (Figs 4 and 5 , Table S1). Projections from the lateral parabrachial nucleus to the CeA may be essential for sodium intake [ 48 – 50 ].…”
Section: Discussionmentioning
confidence: 54%
“…Based on this, we speculate that concurrent CeA and BNST input to the PAG could drive the threshold-like mechanism underlying context-dependent flight behavior (Nagy and Paré, 2008). Alternatively, BNST projections to the CeA may represent necessary inputs to drive CeA CRH+ neurons to gate flight behavior (Fadok et al, 2017; Gungor et al, 2015; Gungor and Paré, 2016; Yamauchi et al, 2018). Future work should investigate these pathways and their potential role in mediating flight behavior in the SCS paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…Current-clamp recordings were conducted to characterize dlBNST neurons. Hyperpolarization-activated cation current (I h ) was identified as described previously (Yamauchi et al, 2018). Specifically, the occurrence of I h was verified by the presence of a "voltage-sag" equal to or Ͼ10% of the total voltage deflection upon the hyperpolarizing current injection, which elicited a membrane voltage of ϳϪ100 mV.…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that ϳ80% of the VTA-projecting dlBNST neurons are type III (Yamauchi et al, 2018). Thus, sIPSCs were recorded from the VTA-projecting dlBNST type III neurons 2 and 4 weeks after the SNL or sham surgery (Fig.…”
Section: Sipscs Increase In Vta-projecting Dlbnst Neurons Of the Chromentioning
confidence: 98%